Laparoscopic removal of an aberrant acupuncture needle in the gluteus that reached the pelvic cavity: a case report - Akira Yamamoto; Junichiro Hiro; Yusuke Omura; Takashi Ichikawa; Shozo Ide; Hiroki Imaoka; Hiromi Yasuda; Hiroyuki Fujikawa; Yoshiki Okita; Takeshi Yokoe; Masaki Ohi; Yuji Toiyama (Surgical Case Reports, 2021)
Abstract Background Intrapelvic aberrant needles are rare in clinical practice. Long-term foreign bodies in the abdominal cavity may form granulation tissue or an abscess, and may cause organ injury. Therefore, such foreign bodies need prompt removal. Case presentation A 26-year-old male athlete was referred to our hospital for investigation of an aberrant acupuncture needle in the gluteus. The needle was unable to be removed during acupuncture treatment, and the end broke off and remained in the gluteus. Abdominal X-ray examination showed a thin, 40-mm-long, metallic foreign body resembling an acupuncture needle. Abdominal computed tomography showed an abnormal shadow in the gluteus. However, it was unclear whether the tip of the needle reached the pelvic cavity. Thus, it was decided to surgically extract the needle via laparoscopic surgery under X-ray guidance as a safe and minimally invasive method. Although X-ray fluoroscopy confirmed that the aberrant needle was located in the gluteus, the needle could not be felt with the forceps, as the peritoneum surrounding the needle had granulomatous changes due to inflammation. Therefore, the retroperitoneum was further dissected to search for the needle. Once the needle was identified, its flexibility enabled it to be easily removed by grasping it directly with a needle holder. The length of the aberrant needle was 40 mm. The postoperative course was uneventful, and the patient was discharged from hospital on postoperative day 2. Conclusions When a foreign body remains in the gluteus and its tip touches intrapelvic organs, such as the rectum, it is critical to determine the best approach for its safe removal. Given the anatomical location of the foreign body and the patient background, laparoscopic removal was considered the best approach in the present case.